Revising nursing home design standards and regulations in the context of an aging population: insights from smart care buildings - Teng, Xiao; Shen, Zhenjiang; Zhang, Yuntian; Ueno, Arisa; Murata, Akira (Frontiers in Public Health, 2025)
In this study, based on the use of smart devices in nursing home, recommendations are made for optimizing existing regulations and standards in Japan. Japan’s housing standards and legal regulations for older population in the context of aging are reviewed firstly, existing regulations and standards are summarized to meet the demands of older population’s housing; the selection of smart medical devices that will effectively be introduced will be based on the demands of older population’s housing. The smart medical devices proposed in this study can be integrated with Japan’s older population’s housing model to enhance the content of existing regulations. Ultimately, a method and a list of improvements to current regulations based on the use of smart devices is proposed. With improved of the regulations, it is possible to eliminate the problem of shortage of personnel in nursing homes, improve work efficiency, and promote cooperation between facilities and care staffs.